Isolation and characterization of a novel bacterium Pseudomonas aeruginosa for biofertilizer production from kitchen waste oil. Issue 73 (17th December 2018) - Li, Ying; Cui, Ting; Wang, Yaxin; Ge, Xizhen
Abstract : Kitchen waste oil is composed of long chain triglycerides (LCTs) that has high energy density. Abstract : Kitchen waste oil is composed of long chain triglycerides (LCTs) that has high energy density. However, it is hard to be degraded by microbes, thereby leading to increasing levels of environmental pollution due to landfill disposition. In this study, we isolated and characterized a novel bacterium Pseudomonas aeruginosa PA-3 that could convert kitchen waste oil into biofertilizer. PA-3 could survive on trilaurin or kitchen waste oil as the sole carbon source, and 10 g L −1 trilaurin or kitchen waste oil was completely consumed within 7 days. Interestingly, the degradation products of kitchen waste oil can be used as biofertilizer in promoting cabbage growth. The plant height, leaf area and stem diameter of cabbage plants were all increased with the addition of kitchen waste oil cultivation products into the soil. Kitchen waste oil degradation products were analyzed by gas chromatography mass spectrometry (GC-MS), and short chain alcohols or fatty acids were observed to be the main products. To unravel the mechanism underlying the accelerated cabbage growth, bacterial diversity of the soil was investigated after using this biofertilizer. Results showed that agricultural probiotics accumulated with the addition of kitchen waste oil cultivation products. Finally, the whole genome of PA-3 was sequenced and analyzed, which showed the existence of a complete β-oxidation pathway in the genome of PA-3. To our knowledge, this is the first study on kitchen waste oil degradation and re-utilization by bacteria, which provides a new method for waste source re-utilization.